(untitled) (Journal of Bio-Science, 2011)
Context: Genetic diversity is pre-requisite for any crop improvement programme as it helps in the development of superior recombinants. Objectives: Recognizing the importance of genetic diversity in plant breeding experiments, the present research work was taken up to estimate genetic diversity in different accessions of rice for various agro-economically important characters. Materials and Methods: Experiments were carried out with 40 Rice (Oryza sativa L.) genotypes which were evaluated for yield and yield contributing traits in Kharif-2007-08. The data were recorded on 10 randomly selected plants from each replication for 12 quantitative characters studied. However days to 50% flowering was recorded on per plot basis. Mean values were subjected to analysis of variance to test the significance for each character. The genetic divergence was estimated and the grouping of the genotypes into cluster was done. Results: Sufficient amount of variability was found in the entire gene pool for all traits studied. The higher magnitude of genotypic and phenotypic coefficients of variation was recorded for plant height, grain yield per hill, harvest index and biological yield per hill. High heritability along with high genetic advance as percent of mean was registered for harvest index, grain yield, plant height, biological yield, test weight, number of tillers per hill and number of spikelets per panicle suggesting preponderance of additive gene action in the expression of these characters. On the basis of Mahalanobis D2 statistics the genotypes were grouped into seven clusters. Plant height, biological yield and test weight contributed considerably, accounting for 86.16 % of total divergence. The genotypes superior in some clusters may be involve in a multiple crossing programme to recover transgressive segregants with high genetic yield potential and early maturity. Conclusion: The promising genotypes selected from diverse clusters should be involved in the hybridization programme in order to transfer some of the desirable yield contributing characters consisted by them. Key words: Rice (Oryza sativa); genetic variability; diversity; clustering pattern DOI: 10.3329/jbs.v17i0.7110 J. bio-sci. 17: 77-82, 2009